DETERMINATION OF WEIGHT FACTORS OF QUALITY INDICES OF PARTICLEBOARDS - Mihajlova, Julia; Trichkov, Neno; Evstatiev, Tsvetelin (Innovation in Woodworking Industry and Engineering design, 2013)
The quality of each product is a set of a great number of indices and characteristics that define its ability to meet the consumers’ requirements. By means of survey of specialists, the more important indices determining the quality of particleboards were ranked and weight factors for each index were calculated. With these weight factors, the determination of composite quality index of PBs will be possible. The results also give guidelines for improvement of the quality of this type of material.